Das verunsicherte Europa - Hoffmann, Hilmar; Kramer, Dieter; Hobsbawm, Eric; Konrad, Gyorgy; Margwelaschwili, Giwi; Zimmerli, Walther C.; Böckenförde, Ernst-Wolfgang; Reich, Jens; Sennett, Richard; Miegel, Meinhard; Beland, Hermann; Leggewie, Claus; et al. (Frankfurt am Main : Verlag Anton Hain, 1992)
In diesem Buch werden die wichtigsten Beiträge der Römerberg-Gespräche 1992 vorgelegt.
boek
Keywords: Europa